2014
DOI: 10.5941/myco.2014.42.2.189
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase Inhibitors from the Fermentation Broth of Phellinus linteus

Abstract: During a search for neuraminidase inhibitors derived from medicinal fungi, we found that the fermentation broth of Phellinus linteus exhibited potent neuraminidase inhibitory activity. Through bioassay-guided fractionation, two active compounds were purified from the ethyl acetate-soluble portion of the fermentation broth of P. linteus. These structures were identified as inotilone (1) and 4-(3,4-dihydroxyphenyl)-3-buten-2-one (2) by spectroscopic methods. Compounds 1 and 2 inhibited H1N1 neuraminidase activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 18 publications
2
20
0
Order By: Relevance
“…In the 13 C NMR spectrum, twelve carbons at δ 187.0, 180.9, 148.4, 145.7, 144.6, 125.0, 123.1, 118.2, 116.2, 112.3, 105.7, and 15.9 were evident. These spectral data were in good agreement with inotilone reported in the literature [ 20 , 21 ]. Consequently, compound 2 was identified as inotilone.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…In the 13 C NMR spectrum, twelve carbons at δ 187.0, 180.9, 148.4, 145.7, 144.6, 125.0, 123.1, 118.2, 116.2, 112.3, 105.7, and 15.9 were evident. These spectral data were in good agreement with inotilone reported in the literature [ 20 , 21 ]. Consequently, compound 2 was identified as inotilone.…”
Section: Resultssupporting
confidence: 91%
“…The 1 H NMR spectrum of compound 3 in CD 3 OD exhibited signals of five methines at δ 7.51 (d, J = 16.4 Hz), 7.07 (d, J = 2.4 Hz), 6.98 (dd, J = 2.4, 8.4 Hz), 6.78 (d, J = 8.4 Hz), and 6.54 (d, J = 16.4 Hz) and one singlet methyl at δ 2.32. These spectroscopic data matched well with 4-(3,4-dihydroxyphenyl)-3-buten-2-one, which was previously isolated from the culture broth of this strain and identified as a neuraminidase inhibitor [ 21 ].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…This role has been attributed to the biological activity of its various components, including polysaccharides, triterpenoids, polyphenols, and pyrans. Based on modern pharmacological studies, P. linteus is reported to have multifaceted biological activities, including anti-inflammatory [6,7,8,9,10,11,12,13,14], immunomodulatory [15,16,17,18,19], antioxidative [20,21,22,23,24,25,26], antimicrobial, and antiviral [27,28,29,30,31,32,33], as well as anticancer [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57], antidiabetic [58,59,60,61,62,63,64,65,66,67], hepatoprotective […”
Section: Introductionmentioning
confidence: 99%
“…They produce various classes of bioactive secondary metabolites with unique chemical structures [ 5 6 ]. In previous studies, we reported the isolation of neuraminidase inhibitors from Phellinus baumii and P. linteus and their biological properties [ 7 8 9 ]. As part of an ongoing effort to identify neuraminidase inhibitors from medicinal fungi, we found that the methanolic extract of fruiting bodies of P. igniarius exhibited significant H3N2 neuraminidase inhibitory activity.…”
mentioning
confidence: 99%